1973
DOI: 10.1111/j.1365-2265.1973.tb00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma testosterone and androstenedione after orchiectomy in prostatic adenocarcinoma

Abstract: SUMMARYOrchiectomy is often used in the management of metastatic adenocarcinoma of the prostate, an androgen dependent tumour, since it markedly reduces the concentrations of plasma testosterone (to a mean level of 28 ± 16 (SD) ng/100 ml) and temporarily inhibits the growth of the neoplasma.In some orchiectomized patients, however, the values of plasma testosterone and androstenedione do not drop to these levels, but remain higher, around 137 ± 23 ng/100 ml and 213 ± 39 ng/100 ml respectively.In these patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 20 publications
3
12
1
Order By: Relevance
“…The testosterone concentrations in the pe ripheral plasma of patients with carcinoma of the prostate reported here are in agreement with the data contained in the literature 0Gandy and Peterson, 1968;Sciarra et al, 1973;Cowley et al, 1976;Harper et al, 1976) and indicate that Leydig cell function in these patients is within the normal range of old men. All the patients with varicocele studied here and those reported on in the literature (Comhaire and Vermeulen, 1975;Swerdloff and Walsh, 1975) had normal plasma testoster one values.…”
Section: Discussionsupporting
confidence: 92%
“…The testosterone concentrations in the pe ripheral plasma of patients with carcinoma of the prostate reported here are in agreement with the data contained in the literature 0Gandy and Peterson, 1968;Sciarra et al, 1973;Cowley et al, 1976;Harper et al, 1976) and indicate that Leydig cell function in these patients is within the normal range of old men. All the patients with varicocele studied here and those reported on in the literature (Comhaire and Vermeulen, 1975;Swerdloff and Walsh, 1975) had normal plasma testoster one values.…”
Section: Discussionsupporting
confidence: 92%
“…Sciarra et al (19) reported that castration reduced circulating levels of testosterone by approximately 90%. The decrease in renal secretory ability showed by castrated animals in our study is in agreement with the expected effect from a reduction in testosterone circulating levels.…”
Section: Discussionmentioning
confidence: 99%
“…This period was chosen because 10 days after castration, the serum concentration of testosterone declines by 90% (19). The experimental procedure followed in the kinetic analysis was the same as described above.…”
Section: Effect Of Orchiectomy On Pah Kinetics In Ratsmentioning
confidence: 99%
“…It appears that they cannot be suppressed below a baseline of approximately 20% of pretreatment A and DHA concentrations (12,16). This residual baseline could result either from direct adrenal secretion, desulfuration of a chronic non-ACTH dependent pool of DHAS, or both.…”
Section: Acth Dexamethasone and Aasmentioning
confidence: 94%
“…These data are summarized in Table 2. Sciarra et al (12) administered 2 mg dexamethasone orally to 10 men 2 months after orchiectomy for prostatic carcinoma. Their serum A decreased 80% from 2.1 ng/ml to 0.43 ng/ml as determined by competitive protein-binding assay.…”
Section: Acth Dexamethasone and Aasmentioning
confidence: 99%